2018
DOI: 10.1021/acsami.8b00072
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Biocatalysts of Cyt c@ZIF-8/GO Composites with High Recyclability via a de Novo Approach

Abstract: To improve the stability and recyclability of enzymes immobilized on metal-organic frameworks (MOFs), graphene oxide (GO) with surface oxygen-rich functional groups was selected to form ZIF-8/GO nanocomposites with the zeolitic imidazolate framework (ZIF-8) for cytochrome c (Cyt c) immobilization. It was found that the functional groups on the GO surface were involved in the growth of ZIF-8 without affecting the crystal structure but their particle size was reduced to about 200 nm. The storage stability and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 51 publications
(108 reference statements)
1
37
1
1
Order By: Relevance
“…We then evaluated the release efficiency of cyt c from cyt c@NKMOF-101-M, and the results indicated that cyt c could be completely released within 30 sfrom NKMOF-101-Mu nder mild conditions (for example,M ES buffer, pH 6.0; Supporting Information, Figure S5 and Table S2). [28][29][30] We also calculated and measured the concentration of metal ion and organic linker after the dissolution of MOFs.L ow concentrations of metal ion (0.67 mgmL À1 of Zn 2+ )and ligand (1.15 mgmL À1 of squaric acid) were observed, indicating trace amounts of impurities introduced. On the contrary,t he wellstudied MOF supports,ZIF-8 and ZIF-90, cannot disintegrate under this mild condition.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…We then evaluated the release efficiency of cyt c from cyt c@NKMOF-101-M, and the results indicated that cyt c could be completely released within 30 sfrom NKMOF-101-Mu nder mild conditions (for example,M ES buffer, pH 6.0; Supporting Information, Figure S5 and Table S2). [28][29][30] We also calculated and measured the concentration of metal ion and organic linker after the dissolution of MOFs.L ow concentrations of metal ion (0.67 mgmL À1 of Zn 2+ )and ligand (1.15 mgmL À1 of squaric acid) were observed, indicating trace amounts of impurities introduced. On the contrary,t he wellstudied MOF supports,ZIF-8 and ZIF-90, cannot disintegrate under this mild condition.…”
Section: Angewandte Chemiementioning
confidence: 99%
“… 67 , 71 Cyt C is secreted into the cytosol and induces apoptosis through a Mc pathway. 59 , 110 , 111 Cyt C aptamers have been attached on the outside of smart mesoporous silica-encapsulated gold nanorods 67 and bacterial magnetic nanoparticles 71 to allow them to efficiently accumulate in the Mc of cancer cells. Mc-targeting aptamers are a prospective strategy for St-Mc-DDSs.…”
Section: Targeting Characteristics Of St-mc-ddssmentioning
confidence: 99%
“…[92] In addition, Zhu and co-workers recently found that there is a synergistic effect between ZIF-8 and graphene oxide (GO) as immobilized enzyme carriers (Figure 5d, i). [93] The cytochrome c (Cyt c)-ZIF-8/GO nanocomposites were synthesized by mixing the methanol solution of Cyt c, GO, Zn(NO 3 ) 2 , 2-HmIm and reaction for 24 h at room temperature. FESEM, XRD, TEM, FTIR and XPS were used to characterize CytZIF-8/GO.…”
Section: Synergistic Properties With Other Materialsmentioning
confidence: 99%